MRNA-Sequencing Identifies Liver as a Potential Target Organ for Triphenyl Phosphate in Embryonic Zebrafish. (31st July 2019) - Reddam, Aalekhya; Mitchell, Constance A; Dasgupta, Subham; Kirkwood, Jay S; Vollaro, Alyssa; Hur, Manhoi; Volz, David C
Abstract: Triphenyl phosphate (TPHP) is a commonly used organophosphate flame retardant and plasticizer in the United States. Using zebrafish as a model, the overall objective of this study was to identify potential organs that might be targeted by TPHP during embryonic development. Based on mRNA-sequencing, TPHP exposure from 24 to 30 h post fertilization (hpf) and 24 to 48 hpf significantly affected the abundance of 305 and 274 transcripts, respectively, relative to vehicle (0.1% DMSO) controls. In addition to minor effects on cardiotoxicity- and nephrotoxicity-related pathways, ingenuity pathway analysis (IPA) of significantly affected transcripts within 30- and 48-hpf embryos revealed that hepatotoxicity-related pathways were strongly affected following exposure to TPHP-alone. Moreover, although pretreatment with fenretinide (a retinoic acid receptor agonist) mitigated TPHP-induced pericardial edema and liver enlargement at 72 and 128 hpf, respectively, IPA revealed that fenretinide was unable to block TPHP-induced effects on cardiotoxicity-, nephrotoxicity-, and hepatotoxicity-related pathways at 48 hpf, suggesting that TPHP-induced effects on the transcriptome were not associated with toxicity later in development. In addition, based on Oil Red O staining, we found that exposure to TPHP nearly abolished neutral lipids from the embryonic head and trunk and, based on metabolomics, significantly decreased the total abundance of metabolites—including betaine, a known osmoprotectant—at 48 and 72 hpf. Overall, our data suggest that, in addition to the heart, TPHP exposure during early development results in adverse effects on the liver, lipid utilization, and osmoregulation within embryonic zebrafish.